Informal Interference in the Judiciary in New Democracies: A Comparison of Six African and Latin American Cases - Mariana Llanos; Cordula Tibi Weber; Charlotte Heyl; Alexander Stroh (German Institute of Global and Area Studies (GIGA), 2014)
This paper assesses the extent to which elected power holders informally intervene in the judiciaries of new democracies, an acknowledged but under-researched topic in studies of judicial politics. The paper first develops an empirical strategy for the study of informal interference based on perceptions recorded in interviews, then applies the strategy to six third-wave democracies, three in Africa (Benin, Madagascar and Senegal) and three in Latin America (Argentina, Chile and Paraguay). It also examines how three conditioning factors affect the level of informal judicial interference: formal rules, previous democratic experience, and socioeconomic development. Our results show that countries with better performance in all these conditioning factors exhibit less informal interference than countries with poorer or mixed performance. The results stress the importance of systematically including informal politics in the study of judicial politics.
Keywords: 300; judicial politics; constitutional court; supreme court; Latin America; Francophone Africa; democratization; separation of powers; informal politics